Predictive significance of the blood eosinophilia for chronic sinusitis with nasal polyp recurrence: A systematic review and meta-analysis: Predictive of the blood eosinophilia for chronic sinusitis - Latif Omer, Goran (Cellular and Molecular Biology, 2024)
Chronic sinusitis with nasal polyps (CRSwNP) is a complex inflammatory condition characterized by recurring nasal polyps, often necessitating repeated interventions. Blood eosinophilia has emerged as a potential biomarker for predicting disease recurrence. The present study aims to assess the predictive significance of blood eosinophilia for the recurrence of nasal polyps. To accomplish this objective, we employed the appropriate search keywords to explore international databases such as Web of Science, PubMed, Embase, and Scopus. Through this process, we extracted scholarly articles that assessed the prognostic value of blood eosinophilia in the recurrence of nasal polyps. The statistical software STATA (version 15) was employed, along with random and fixed-effects models, to appraise the compiled data. Nine articles met inclusion criteria, with a total sample size of 1279 individuals (569 recurrent polyp individuals and 710 non-recurrent polyp individuals). Cumulative Odds ratio analysis revealed that CRSwNP is associated with high blood eosinophile percentage compared to the non-CRSwNP group (p=0.01, OR=1.26, 95%Cl (1.15,1.36). The cut-off value of blood eosinophil percentage (>0.78) had relatively good, and statistically significant predictive potential. No significant publication bias was observed for the included studies. Our findings indicate that the utilization of blood eosinophils holds significant predictive value and can serve as a valuable tool for detecting recurrence in patients with CRSwNP. Based on the outcomes of our comprehensive analysis, we propose a threshold of >0.78 as a reliable indicator for assessing the probability of recurrence in CRSwNP patients.